Teachers’ belief in managing classroom : Indonesian context - Yasyir Fahmi Mubarak; Muthia Farida; I Made Wilatara (STKIP PGRI Banjarmasin, 2017)
Research in this past 30 years has suggested that teachers’ beliefs heavily influence their pedagogical practice. Beliefs also defined as personal theories or concepts. This definition is influenced by the constructivism psychologists who recognize that every individual has his/her own ways of processing the understanding, and beliefs as the results of self-construction. Beliefs may reflect in teachers’ teaching. Factors that drive belief include early experiences as learners, experiences in professional coursework, constextual factors, and reflection on teacher’s past practices This study is aimed to reveal how teachers’ manage their classroom and teachers’ belief as well. A descriptive qualitative study is conducted by using observation and questionaire. Teachers from different school and background were choosen in this study.